The Potentiality of Crassocephalum crepidioides for Phytoremediation of Cd Contaminated Soil under the Application of EDTA. Issue 1 (March 2021) - Cheng, Dandan; Liu, Xixi; Zhang, Hui; Zou, Ziwei; Zhu, Guangxu
Abstract: Aiming to identify measures to improve the cadmium (Cd) extraction efficiency of Crassocephalum crepidioides on Cd contaminated soil, a pot experiment was conducted to investigate plant growth and Cd accumulation in Crassocephalum crepidioides enhanced by ethylenediaminetetraacetic acid (EDTA) application. The results revealed that plant growth was inhibited and biomass decreased while treated with EDTA. The application of EDTA activated Cd in soil, thus increasing the Cd concentration of leaf, stem and root of Crassocephalum crepidioides by 10%∼91%, 13%∼98%, 20∼93%, respectively. According to the Cd extraction amount by the plant, potential phytoremediation capability of Crassocephalum crepidioides in Cd contaminated soils would be enhanced effectively with application of 4 mmol⋅kg −1 EDTA, however, the environmental risks should be considered synthetically when using. This study can provide a basis for the remediation of Cd contaminated soil.